Sparse Phase Retrieval of One-Dimensional Signals by Prony's Method - Beinert, Robert; Plonka, Gerlind (Frontiers in Applied Mathematics and Statistics, 2017)
In this paper, we show that sparse signals f representable as a linear combination of a finite number N of spikes at arbitrary real locations or as a finite linear combination of B-splines of order m with arbitrary real knots can be almost surely recovered from O (N 2 ) intensity mea- surements □□□□F[f ](ω)□□□□2 up to trivial ambiguities. The constructive proof consists of two steps, where in the first step the Prony method is applied to recover all parameters of the autocorre- lation function and in the second step the parameters of f are derived. Moreover, we present an algorithm to evaluate f from its Fourier intensities and illustrate it at different numerical examples.